Credibly conveyed and genuinely received: Reconciliation and the South African TRC revisited - Earl, Derek J. R (University of Ottawa (Canada), 2005)
This thesis revisits the South African Truth and Reconciliation Commission (TRC) to explore societal-level reconciliation viewed as the reconstruction of identity. It argues that narrative processes of identity construction can contribute in a positive way to reconciliation when a message of reconciliation is credibly conveyed and genuinely received. This means that a message of reconciliation is communicated, that the content of the message responds to the needs of the socio-cultural context, and that the message has been understood and accepted. The TRC message of reconciliation is embodied in themes of human rights, forgiveness, and ubuntu which offer a vision to a peaceful, inclusive South Africa. The conclusions reached suggest some positive indicators of a developing process of reconciliation, but the long-term success of the construction of a peaceful, democratic, and inclusive South Africa will also be a function of success in the political and socio-economic sectors.
Keywords: Political Science, International Law and Relations.